(untitled) (Altre Modernità, 2013)
This paper focuses on the different representations of the Apocalypse in one of the literary genre which has greatly increased in Latin America during the last decades: the “microficción” or flash fiction. In this very short texts the Apocalypse is taken as a central theme in its various meanings: in the greek one, as “revelation of the truth”, in the biblical eschatological one, concerning the ultimate destiny of mankind, or in the sense that it has acquired in modern times, as “narrative of the end”, generally related to a catastrophic or dystopic imagery. Through the close reading of a wide number of texts written by Latin American contemporary authors such as Raúl Brasca, Rosalba Campra, Rogelio Guedea, Ana María Shua and others, we intend to point out in which way the apocalyptic inspiration, due to the peculiar construction of the flash fiction -that requires a special connection between the incipit and the ending, because of its reduced dimensions- works at the same time on two levels: the semantic one and the formal one. In particular, we’ll dwell upon that special effect of revelation of a hidden truth caused by the surprise ending so distinctive of this genre.